Upaya Meningkatkan Keterampilan Menulis Puisi Menggunakan Model Kooperatif Tipe Think Talk Write ( TTW ) Di Sekolah Dasar - Jais, Ahmad (Science and Education Journal (SICEDU), 2024)
This research is motivated by the low interest of students in writing poetry in Indonesian language learning in the class of SD Negeri 007 Rambah Hilir. One solution to overcome this problem is to use a Think, Talk, Write (TTW) type cooperative model. Thus, the aim of this research is to improve poetry writing skills using the think, talk, write (TTW) type cooperative model in Indonesian language learning for class III elementary school. This research method uses classroom action research (PTK) which is carried out in two cycles and each cycle is carried out two meetings. This research was carried out at SD Negeri 007 Rambah Hilir with the research subjects being third grade elementary school students. Data collection in this research used observation and documentation techniques. Increasing students' problem solving abilities in Indonesian language subjects from before the action with an average percentage of 51.45% in the poor category, using the think, talk, write (TTW) type cooperative model method ) then there was an increase in cycle I with a percentage of 83.92%, while on average in cycle 2 the ability to improve poetry skills using the think, talk, write (TTW) type cooperative model increased with an average of 100%. So, learning Indonesian to improve poetry writing skills using the think, talk, write (TTW) type cooperative model can improve the writing skills of class III students at SD Negeri 007 Rambah Hilir.